FAKTOR YANG BERHUBUNGAN DENGAN HIPEREMESIS GRAVIDARUM PADA IBU HAMIL DI KLINIK SIKAMALI TAHUN 2024 - Putri Ervina Hartini (CV. Denasya Smart Publisher, 2025)
Introduction: Hyperemesis gravidarum (HG) is a pregnancy complication characterized by excessive nausea and vomiting, potentially leading to dehydration, electrolyte imbalance, and metabolic disturbances, which can endanger both mother and fetus. At Klinik Sikamali, HG cases increased from 27 in 2023 to 33 in 2024, indicating a growing maternal health concern. Methods: This was a descriptive quantitative study with a cross-sectional approach. The sample consisted of 60 pregnant women who were hospitalized at Klinik Sikamali in 2024. Data were collected from medical records and analyzed using the Chi-square test. Results: Most of the toddlers with diarrhea at the Bantul 1 Health Center are aged 24-59 months (50%), with female sex (52.8%), the majority of mothers with diarrhea are working (58.3%), moderate education (63.9%), and in the age range of 20-35 years (66.7%). Whereas for toddlers without diarrhea at the Bantul 1 Health Center the majority are aged 24-59 months (70%), male sex (59%), most mothers do not work (58.5%), mothers with medium education (57.6%), and in the age range of 20-35 years (63.6%). Conclusion: The results of the study concluded that the majority of toddlers with diarrhea and without diarrhea were aged 24-59 months, for toddlers with diarrhea the majority were women who had working mothers while the children who did not have diarrhea were mostly boys with mothers who did not work/IRT. The majority of toddlers with diarrhea and without diarrhea have moderately educated mothers (SLTA) with a mother's age range of 20-35 years.